THE RELATIONSHIP OF MATERNAL COMPLEMENTARY FEEDING KNOWNLEDGE, ATTITUDE ON CHILD WEIGHT AT JEMBER REGENCY - Ulfia Fitriani Nafista; Nuzul Qur’aniati; Lailil Fatkuriyah; Ainul Hidayati; Umi Sukowati (Universitas Kusuma Husada Surakarta, 2025)
Malnutrition is still one of the problems in Indonesia. Good feeding is one of the important indicators in preventing children from experiencing malnutrition. Nutritional problems in children can cause long-term problems such as growth disorders, non-optimal brain development. Feeding problems can be leveled from the provision of complementary breastfeeding. The purpose of this study is to assess the mother's knowledge and attitudes related to complementary breastfeeding and its relationship with children's weight. The method used in this study is purposive sampling with a total sample of 130 mothers conducted in Jember district. It was found that mothers who have knowledge and positive attitudes have children with ideal weights according to the age of the child.